STATISTICAL DATA SERVICE SYSTEM (SIPEDAS) IN BPS NORTH SULAWESI PROVINCE WEBSITE-BASED - Pandoh, Kevin Mclaren; Rantung, Vivi Peggie (Jurnal Teknik Informatika (Jutif), 2024)
The Central Bureau of Statistics (BPS) is important in providing high-quality statistical data to various parties. The demand for accurate and timely data is increasing in this digital era. This research aims to develop a Website-Based Statistical Data Service System (SIPEDAS) application using the Rapid Application Development (RAD) method to speed up design and ensure the system meets user needs. The RAD method consists of four stages in application development: requirements planning, system design, development process, and implementation. Data collection was conducted through interviews with mentors and sourcing data from the BPS WebAPI. Following these stages can produce an application that meets user expectations. After testing, it can be concluded that this application makes it easier for users to search for information, news, infographics, and publications needed without having to visit the North Sulawesi BPS Office directly.